To solve the equation \(3x + 5y = 60\) for \(y\), we can follow these steps:
Step 1: Isolate \(5y\)
We start with the original equation:
\[
3x + 5y = 60
\]
Subtract \(3x\) from both sides:
\[
5y = 60 - 3x
\]
Step 2: Solve for \(y\)
Now, divide both sides by \(5\):
\[
y = \frac{60 - 3x}{5}
\]
This can be rewritten as:
\[
y = 12 - \frac{3}{5}x
\]
Summary:
From the options provided:
- Response: \( y = 60 - 3x \)
However, none of the choices directly match the simplified solution as it is not expressed in terms of dividing \(60 - 3x\) by \(5\).
The closest option, related to isolating \(y\), would be:
- \( y \text{ is equal to } 60 - 3x \)
But for clarity and correctness, this is the solution we derived:
\[
y = 12 - \frac{3}{5}x
\]
However, based on your options, the most appropriate response for isolating \(y\) would be:
- y = 60 - 3x (if we consider that as the primary expression before division for 5).
Let me know if there is anything more specific you need!